Enhancing Corporate Governance Through Shareholder Activism - Sampath, Srinivasan (2008)
India as a developing country needs to be reformed at equal intervals to maintain growth and stability in an economy. The scandals and issues in the stock market highlighted the need for corporate governance. In western countries shareholder activism gained importance due to the scandals and the reforms being very effective now. This paper is aimed to review the history of corporate governance and the issues faced in India. There are major reforms initiated in 1990s to ensure corporate governance is followed effectively by corporate. The research will help to find out the status of shareholder activism in India. I examined the policies laid by SEBI and the governance committees recommendations. I have also analyzed the policies followed by the good governance companies and bad governance companies and have tried to research on corporate issues and find out a possible solution and mechanism to improve corporate governance. The recommendation to enhance corporate governance will be focused mainly on shareholders activism.